ASEAN Economic Community and Legal System Readiness in the Field of Agriculture - Sastroatmodjo, Sudijono (Law Research Review Quarterly, 2015)
The ASEAn economic community which will take place at the end of 2015, for Indonesia can be an opportunity, but it can also be a very formidable challenge. This is related to the objective reality of Indonesia compared to other ASEAN member countries, namely that Indonesia has the most extensive area and the most population. With these conditions, Indonesia has many opportunities in the ASEAN Economic Community, including as a potential global market and an investment destination country.